Techniques of reordering traces in the event logs in business process management tasks - Chalyi, Serhii Fedorovich; Bogatov, Evgen Olegovich; Pribylnova, Inna Borisovna (Vestnik Nacionalʹnogo tehničeskogo universiteta "HPI". Seriâ Sistemnyj analiz, upravlenie i informacionnye tehnologii (Online), 2018)
The problem of formation of input data for construction of models of business processes by methods of the intellectual analysis of processes is studied. It is shown that event logs of real information systems do not always meet the requirements of the ordering of input data on processes, that is, a log can have one track with events from different business processes. The tasks of analysis of trace characteristics in the business process event log and the development of methods for forming process events information order tracks organized on the basis of the comparison of event attributes and on the basis of comparison with the invariants of the event attributes of the business process logs are organized in the processes of the log of events events of the process management information system. The first method generates business process log lines based on pairwise comparison of event attributes based on the criterion for maximizing the number of shared attribute values for this pair. The method sequentially selects events from the common path for several business processes, and after pairwise comparison of the attributes with the events of the traces of specific business processes, determines the belonging of the next event to the path of the corresponding process. When comparing, the end event of the business process is also detected. The second method generates log lines based on the comparison of the invariant of the event attributes and the event, which is analyzed by the criterion of maximizing the weight of the values of the common attributes. Unlike the first method, when choosing a new business process, an invariant is created in the form of a sum of weights of the values of the attributes of the log of the business process. The scales of attribute values reflect the number of occurrences of these values in the execution of the business process. This allows you to take into account the history of the implementation of the business process in implementing the method. In practical terms, both proposed methods allow the formation of a set of business process event logs that are executed in parallel in a format suitable for use of methods and technologies of the intellectual analysis of proces ses. The first method has a lower accuracy. However, its advantage is the ability to use in the presence of only a joint path of several business processes, without the previously known orderly traces log of each business process. The second method allows you to increase the accuracy of the highlighting of the event path for each business process. The disadvantage of this method is that it requires a priori formation of the invariant of the attributes of the business process events.